To the Issue of Clarifying the Chronology and Cultural Features of the Vyatka River Neolithic - Tatiana M. Gusentsova (Археология евразийских степей)
The article deals with generalization and clarification of the Neolithic dating of the Vyatka River. Vyatka River Neolithic dating used earlier in the context of the general chronology of the Neolithic cultures of the Volga-Kama or Middle Urals. In the Neolithic period in the Vyatka River basin there were cultures with different traditions of pottery production: undecorated, stroked, combed and dotted-and-combed ornamentation. The main source for chronology is the dating of organics in ceramics, charcoal and bones. To date, 24 radiocarbon dates have been obtained from 10 sites. The oldest dates are obtained at campsites with undecorated pottery - the beginning of VI millennium BC. The earliest complexes with stroked pottery date from the first half to the middle of the VI millennium BC; the developed ones survive until the second half of the V millennium BC. The earliest sites with combed ceramics date somewhat later than stroked ceramics – the middle-second half of the VI millennium BC. The tradition exists until the second half of the V millennium BC. The appearance of combed-dotted ceramics ware and collar ceramics dates back to the first half – the middle of the V millennium BC. Cultural and chronological features of Neolithic sites indicate their relationship with the forest steppe Volga, Middle Volga and Kama regions.